What happened to heterodox economics in Germany after the 1970s - Arne Heise; Sebastian Thieme (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2015)
In the context of ongoing criticisms of the lack of pluralism in economics, the present article aims to discuss the development of 'heterodox' economics since the 1970s. Following Lakatos's concept of scientific research programs (srp), and concentrating on the situation in Germany, the article will discuss classifications of economics, and will specify the understanding of diversity in the light of 'axiomatic variations' of the economic mainstream. This will form the basis for the subsequent description of the development of heterodoxy in Germany, with special reference to the founding of new universities and the reform movements in the 1970s. It can be shown that the heterodox scene flourished in this period, but that this pluralization remained fragmented and short-lived; by the 1980s at the latest heterodoxy was again on its way to marginalization. The history of heterodoxy in Germany thus presents itself as an unequal 'battle of the paradigms', and can only be told as the story of a failure.
Keywords: A11; B20; B50; Z13; 330; heterodox economics; pluralization; philosophy of science; sociology of science